Travel Time Reliability Analysis on Paratransit, case study: Substação-Muahivire route, Nampula - Mozambique - Fernando, Celso L. (Technium Social Sciences Journal, 2024)
In numerous medium-sized cities in Sub-Saharan Africa, such as Nampula, the reliability of mini-bus travel time is frequently a subject of inquiry. One contributing factor to this uncertainty is the considerable number of stops made throughout the route for passenger-related purpose, including boarding and disembarking. This study utilizes data collected during off-peak periods to scrutinize the day-to-day travel time patterns of mini-buses along the route. The route has been segmented into intervals of 500 meters each, and the analysis focuses on the duration of trips at each segment. The evaluation is based on the Coefficient of Variation (CoV) of travel time, indicating the extent of dispersion in mini-bus travel time at the segment level. The results reveal that the CoVs at nearly all segments along the route are minimal, measuring less than 15%. This suggests that day-to-day variability of travel time at the segment level is negligible. However, on road segments characterized by commercial activities, the CoVs range from 15% to 22%.